ULTRA MICRO FUNDING PROGRAM: SURVEY OF SMALL AND MEDIUM ENTERPRISES - Nurhidayati, Nurhidayati; Muamarah, Hanik Susilowati; Wahyudi, Eri (Kesatuan Press, 2025)
This study aims to determine how MSME actors in Palembang, South Sumatra, perceive MSME credit or financing that the government provides to MSME actors, especially at the micro level. This study uses questionnaires to obtain the perceptions of MSME actors towards MSME financing. The respondents of this study were MSME actors who participated in the “Beli Kreatif Sumatera Selatan (BKSS)” activity, a collaborative program of the Ministry of Tourism and Creative Economy with several stakeholders, one of which is the Ministry of Finance. The results of the questionnaires are then presented descriptively. Based on the questionnaire processing results, several things need attention, especially from MSME financing policymakers. The aspects that received the lowest assessment were regarding the equalization of credit to all levels of MSMEs and the amount of loans offered in the financing. In open questions, most respondents also expect interest-free Sharia financing. This study focuses on exploring the perceptions of MSME actors on financing or debt, which, for most MSMEs, is very difficult to access, especially at the micro level. The study results are expected to improve the design of MSME financing by the government.